2015
DOI: 10.1259/bjr.20140685
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating benign and malignant salivary gland tumours: diagnostic criteria and the accuracy of dynamic contrast-enhanced MRI with high temporal resolution

Abstract: The authors Phong Dai Lam and Ami Kuribayashi equally contributed to this work.Objective: To determine the optimal diagnostic criterion of dynamic contrast-enhanced MRI (DCE-MRI) for predicting salivary gland malignancy using a dynamic sequence with high temporal resolution, as well as the accuracy of this technique. Methods: The DCE-MRI findings of 98 salivary gland tumours (74 benign and 24 malignant) were reviewed. MR images were sequentially obtained at 5-s intervals for 370 s. Two parameters, peak time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Significant differences were found in the mean ADC values between Warthin tumours and pleomorphic adenomas, as well as between Warthin tumours and benign lesions. 17 Motoori et al 26 reported higher ADC values in pleomorphic adenomas than malignant tumours. An ADC cut-off value of 1.315 3 10 23 mm 2 s 21 had sensitivity and specificity of 82.1% and 81.2%, respectively, for distinguishing between pleomorphic adenomas and malignant tumours.…”
Section: Discussionmentioning
confidence: 96%
“…Significant differences were found in the mean ADC values between Warthin tumours and pleomorphic adenomas, as well as between Warthin tumours and benign lesions. 17 Motoori et al 26 reported higher ADC values in pleomorphic adenomas than malignant tumours. An ADC cut-off value of 1.315 3 10 23 mm 2 s 21 had sensitivity and specificity of 82.1% and 81.2%, respectively, for distinguishing between pleomorphic adenomas and malignant tumours.…”
Section: Discussionmentioning
confidence: 96%
“…and malignant parotid lesions (4,(13)(14)(15)(16). However, recent studies have demonstrated a comparable high sensitivity and specificity between these imaging modalities (7,17,18).…”
Section: A B Cmentioning
confidence: 99%
“…Table summarizes how imaging was utilized in this study. There is evidence to suggest that contrast enhanced MRI has comparable diagnostic accuracy to FNAC in differentiating benign from malignant disease . Traditionally, cross‐sectional imaging (ideally MRI) is considered in patients who have clinical or sonographic features of malignancy and lesions with deep lobe extension; it may also have a role in Sal 3 and Sal 4 lesions.…”
Section: Discussionmentioning
confidence: 99%